Realization of quantum secure direct communication over 100 km fiber with time-bin and phase quantum states - Haoran Zhang; Zhen Sun; Ruoyang Qi; Liuguo Yin; Gui-Lu Long; Jianhua Lu (Light: Science & Applications, 2022)
Abstract Rapid progress has been made in quantum secure direct communication in recent years. For practical application, it is important to improve the performances, such as the secure information rate and the communication distance. In this paper, we report an elaborate physical system design and protocol with much enhanced performance. This design increased the secrecy capacity greatly by achieving an ultra-low quantum bit error rate of <0.1%, one order of magnitude smaller than that of existing systems. Compared to previous systems, the proposed scheme uses photonic time-bin and phase states, operating at 50 MHz of repetition rate, which can be easily upgraded to over 1 GHz using current on-the-shelf technology. The results of our experimentation demonstrate that the proposed system can tolerate more channel loss, from 5.1 dB, which is about 28.3 km in fiber in the previous scheme, to 18.4 dB, which corresponds to fiber length of 102.2 km. Thus, the experiment shows that intercity quantum secure direct communication through fiber is feasible with present-day technology.